2010
DOI: 10.1080/01431160903380649
|View full text |Cite
|
Sign up to set email alerts
|

Estimation of tree lists from airborne laser scanning by combining single-tree and area-based methods

Abstract: Individual tree crowns may be delineated from airborne laser scanning (ALS) data by segmentation of surface models or by 3D analysis. Segmentation of surface models benefits from using a priori knowledge about the proportions of tree crowns, which has not yet been utilized for 3D analysis to any great extent. In this study, an existing surface segmentation method was used as a basis for a new tree model 3D clustering method applied to ALS returns in 104 circular field plots with 12 m radius in pine-dominated b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
60
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(62 citation statements)
references
References 36 publications
(25 reference statements)
2
60
0
Order By: Relevance
“…As an alternative to the grid-based approach, use of automatic stand delineation by image segmentation has been studied for defining inventory units (e.g., [8]). Automatic segmentation of ALS data has also been applied for delineating very small segments with a view to detecting individual tree crowns (e.g., [9,10]). In estimating stand level forest attributes (area based approach) the segment size is larger than single tree crowns.…”
Section: Introductionmentioning
confidence: 99%
“…As an alternative to the grid-based approach, use of automatic stand delineation by image segmentation has been studied for defining inventory units (e.g., [8]). Automatic segmentation of ALS data has also been applied for delineating very small segments with a view to detecting individual tree crowns (e.g., [9,10]). In estimating stand level forest attributes (area based approach) the segment size is larger than single tree crowns.…”
Section: Introductionmentioning
confidence: 99%
“…AB and ITC approaches to estimating biophysical attributes are not mutually exclusive, and several authors demonstrated how they can be combined [e.g. Lindberg et al, 2010;Vastaranta et al, 2012].…”
Section: Area-based and Individual Tree Crown Approachesmentioning
confidence: 99%
“…In the second phase, accurately located field trees are linked to the segments , Lindberg et al 2010, Breidenbach et al 2010. In contrast to ITD, it is not assumed that a single segment represents a single tree (see Figure 8).…”
Section: Estimation Of Stand Variables Using a Tree Cluster Approachmentioning
confidence: 99%
“…The TCA does not provide information as detailed as ITD could, in theory, but it is still capable of capturing the spatial variation in stand variables better than ABA. Lindberg et al (2010) used the TCA to predict consistent tree height and stem diameter distributions. Breidenbach et al (2010) obtained a plot-level RMSE of 17.1% for VOL compared to 20.6% with ABA.…”
Section: Estimation Of Stand Variables Using a Tree Cluster Approachmentioning
confidence: 99%